PENGARUH MEDIA SOSIAL TWITTER @WOMANFEEDS_ID TERHADAP PERILAKU KONSUMTIF FOLLOWERS - Sherly Novitasari; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The emergence of the internet has had many influences and changes in human life. The rapid dissemination of information through social media obtained from various sources may have certain effects. Twitter account @womanfeeds_id  as a forum that facilitates the dissemination of information quickly and widely can influence a person's behavior, one of which is consumptive behavior. The purpose of this study was to determine how much influence the social media twitter @womanfeeds_id has on the consumptive behavior of followers.            The method used in this research is an explanative quantitative method. The data collection technique used a questionnaire. The population in this study were all followers of the account @womanfeeds_id. The number of samples for this study were 398 respondents. To determine the effect of the two variables, researchers used simple linear regression analysis. And for data processing, the questionnaire test was carried out using the program. Product and Service Solution statistical (SPSS) Windows version 25.            Based on the results of simple linear regression analysis, the regression coefficient value was obtained in this study with the equation Y = 9.091 + 0.540X with a significance level of 0.000. If the level of significance is smaller than the specified significance of 0.05, it can be concluded that there is an influence of social media twitter @womanfeeds_id on consumptive behavior followers'. The coefficient of determination or R2 in this study was 27.9%, which shows the influence of social media @womanfeeds_id twitter on consumer behavior followers are in a weak category. Meanwhile, the remaining percentage of 72.1% is influenced by other variables not examined in this study. Keyword: Social Media, Twitter, and Consumtive Behavior, followers